Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang Sayur Mayur di Desa Duriaasi Kecamatan Wonggeduku Kabupaten Konawe - Zefy Mardianti; La Ode Alwi; Abdul Gafaruddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This research was to determine the extent of the influence of consumption, investment and the amount of market expenditure on the income of vegetable traders in Duriaasi Village, Wongeduku District, Konawe Regency. The population in this research were all vegetable traders in Duriaasi Village, amounting to 34 people. Non-probability sampling was used in the sampling process, namely through the saturated sampling method (census), in which all the population was sampled. Data analysis used multiple linear regression analysis to determine the effect of consumption, investment and the amount of market expenditure on the income of vegetable traders in Duriaasi Village, Wongeduku District, Konawe Regency. The results showed thatthat the variables of consumption, investment and market expenditure simultaneously have a significant effect on the income of vegetable traders in Duriaasi village. The investment variable partially has a positive and significant effect on the income of vegetable traders in Duriaasi village. Meanwhile, market consumption and expenditure variables have a negative and significant effect on the income of vegetable traders in Duriaasi village.